PRELIMINARY INVESTIGATION OF THE CHEMICAL QUALITY OF DOMESTIC WATER SOURCES IN SELECTED COMMUNITIES OF LANGTANG AREA, PLATEAU STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
A preliminary analysis of the chemical quality of domestic water sources in Langtang area was undertaken to determine variation in quality of water sources and how it meets the Nigerian Standard for Drinking Water Quality (NSDWQ). Using stratified random sampling technique, 50 water samples were taken from five different sources: rain, dams, streams, boreholes and hand dug-wells. Samples were tested in the laboratory for 20 parameters using standard methods described by USEPA (2012) and results subjected to ANOVA and independent sample t-tests. Temperature (28), turbidity (15), Ca (85), Mg (30), Cl (275), Fe (1.2), Pb (0.1) and Cd (0.002) had average mean above limits. ANOVA result shows significant variation in water quality with p-value of 0.001. Post-Hoc test revealed significant variation in 80% of the parameters tested: temperature, turbidity, EC, CaCO3, F, TDS, Ca, Mg, NO3, Fe, Cu, Al, Pb, As and Cd. Only pH, Cl, Mn, Cr and Zn do not show significant variation. Independent sample t-test also show significant variation in water quality to the Nigerian Standard for Drinking Water Quality (NSDWQ), which implies the water is unsuitable for human consumption. This study has demonstrated that despite differences in the protection levels of water sources, some parameters may still be the same across sources. It is therefore recommended that detail analysis of each water source be carried out to identify parameters responsible for pollution, as well as remediation the of water before consumption.
Keywords: Water Sources; Water Quality Variation; Water Safety.